2020
DOI: 10.1530/ec-19-0566
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive follicular thyroid neoplasm with papillary-like nuclear features: a problematic entity

Abstract: Noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) is a borderline thyroid tumour formerly known as noninvasive encapsulated follicular variant of papillary thyroid carcinoma. The prevalence of NIFTP is estimated at 4.4–9.1% of all papillary thyroid carcinomas worldwide; however, the rate of occurrence of NIFTP is eight times lower in Asian countries than in Western Europe and America. At the molecular level, NIFTP is characterised by the lack of BRAF V600E and BRAF V600E-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…Our data clearly demonstrate that NIFTP has telomere signatures similar to FTA that is distinct from classical and follicular variants PTC. Although, NIFTP cannot be considered a benign lesion but rather a low-risk thyroid nodule, our results suggest and reinforce the idea that NIFTP are lesions more closely related to benign thyroid neoplasms, rather than to malignant lesions [18,19].…”
Section: Niftp Has a 3d Profile Similar To Fta And Different From Clasupporting
confidence: 78%
“…Our data clearly demonstrate that NIFTP has telomere signatures similar to FTA that is distinct from classical and follicular variants PTC. Although, NIFTP cannot be considered a benign lesion but rather a low-risk thyroid nodule, our results suggest and reinforce the idea that NIFTP are lesions more closely related to benign thyroid neoplasms, rather than to malignant lesions [18,19].…”
Section: Niftp Has a 3d Profile Similar To Fta And Different From Clasupporting
confidence: 78%
“…The published cases we reviewed exhibited variable echogenicity on US scan. Such hypoechoic, hyperechoic or isoechogenic US findings [ 11 , 14 , 16 ] are supported by others who described NIFTP lesions as well-circumscribed with widely variable echogenicity [ 14 ]. In addition, initial US only showed the left sided complex cystic nodule; only on US guided FNA was the second nodule on the right side identified and aspirated.…”
Section: Discussionmentioning
confidence: 58%
“…In other cases, NIFTP may coexist with a carcinoma. A recent study by Zajkowska et al (2020) revealed that a synchronous malignant lesion could be present in a not negligible percentage of patients with NIFTP (15-46%, mostly papillary thyroid microcarcinomas): if this happens, NIFTP should not be included in TNM staging, as in general, only malignant tumors should be incorporated into the staging systems (Seethala et al 2018).…”
Section: Can a Niftp Be Multifocal?mentioning
confidence: 99%